REVIEW ESSAY - Menzel, Paul T. (Bioethics, 1989)
Rationing Health Care in America:Perceptions and Principles of Justice by Larry R. Churchill. American Health Care:Realities, Rights, and Reforms by Charles J. Dougherty. Should Medical Care Be Rationed by Age? edited by Timothy M. Smeeding, with Margaret P. Battin, Leslie P. Francis, and Bruce M. Landesman, Totowa, N.J., Rowman and Littlefield.